Erythropoietin and its use in pediatric patients [ERITROPOIETIN VE COCUKLARDA KULLANIMI] - (:unkn) unknown (My University, 1996)
EPO is an hormone that is produced by the kidney in response to hypoxia and stimulates erythropoiesis in bone marrow. Since it was cloned and genetically engineered using recombinant DNA technology, it has found various applications in different clinical setting. In this paper, we intend to summarize the biology and clinical use of erythropoietin in pediatric patient population.